(untitled) (INNOVATIVE ECONOMY, 2020)
Babych M.M. TYPES AND CRITERIA OF SHORT SUPPLY CHAINS Purpose. The aim of the study is to establish the basic criteria for short supply chains and the characteristics corresponding to them. Methodology of research. The methodological basis of the research consists of general scientific and specific methods of scientific knowledge. In the process of research, the following methods of economic research were used: abstract-logical (the formation of theoretical generalizations and conclusions); monographic (study of scientific works on the problems of formation of short supply chains); terminological analysis and operationalization of concepts (study of conceptual approaches to the interpretation of the concept of "short supply chains", definition of defining characteristics of short supply chains and their corresponding rice); direct analysis and synthesis (systematization of legislative initiatives of EU member states on the problem under investigation). Findings. A critical analysis of the approaches of scientists to determining the types of short supply chains according to different classification features is made: forms of communication between the consumer and the producer (face to face, spatial proximity, spatial prevalence); traditional and non-traditional; on the basis of the level of compromise adopted by producers and consumers; community-supported agriculture (CSA). Originality. The defining features of short supply chains and their respective features: distances (geographical, social and economic proximity) are established; communication (direct exchange of information); types of sales (direct, collective and partnership); size (large and small SFSC schemes); quality of products (mainly organic, environmentally sustainable); number of intermediaries (missing or no more than one); compromise level (low, medium and high). Practical value. The development of various forms and types of short supply chains allows us to solve the problem of improving nutrition at the local level and gain additional positive influence on the formation of a model of sustainable development of rural areas. Key words: short supply chains; distance; communication; sales; size; product quality; number of intermediaries.